2009
DOI: 10.1016/j.biomaterials.2009.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Enabling customization of non-viral gene delivery systems for individual cell types by surface-induced mineralization

Abstract: Delivering genes to mediate functions of cells is a crucial technology for both basic science and clinical applications. Though numerous non-viral gene delivery systems have been developed, the diversity of mammalian cells poses a great challenge to the material design. Here, we demonstrate that surface-induced mineralization represents a promising approach to systematically customize DNA delivery with respect to the characteristics of cells. We initially examined gene transfer in nine cell types derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 20 publications
0
62
0
Order By: Relevance
“…1), [CH 3 (CH 2 ) 17 ] 2 NCH 2 CH 2 CONHCH 2 CH 2 N(CH 2 CH 2 CONHCH 2 CH 2 NH 2 ) 2 (PD; modified from DL-G1 in [23], supplied by Katayama Chemical Industries, Japan), (2) 2,3-dioleyloxy-N-[2(sperminecarboxamido)ethyl]-n,n-dimethyl-1-propanaminium trifluoroacetate (DOSPA) and dioleoylphosphatidylethanolamine (DOPE) mixed at the mass ratio of 3: 1 (LF; Lipofectamine Ò , Life Technologies, USA), and (3) N-[1-(2,3-dioloyloxy) propyl]-N,N,N-trimethylammonium methylsulfate (DT; DOTAP, Roche, Switzerland). PD is a newly developed Lp [23][24][25], whereas LF and DT are conventional ones used in previous studies [19,20]. As a DNA source, pGL3 control vector (Promega, USA), which was propagated and purified in 0.7-1.2 mg/mL plasmid, was used.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…1), [CH 3 (CH 2 ) 17 ] 2 NCH 2 CH 2 CONHCH 2 CH 2 N(CH 2 CH 2 CONHCH 2 CH 2 NH 2 ) 2 (PD; modified from DL-G1 in [23], supplied by Katayama Chemical Industries, Japan), (2) 2,3-dioleyloxy-N-[2(sperminecarboxamido)ethyl]-n,n-dimethyl-1-propanaminium trifluoroacetate (DOSPA) and dioleoylphosphatidylethanolamine (DOPE) mixed at the mass ratio of 3: 1 (LF; Lipofectamine Ò , Life Technologies, USA), and (3) N-[1-(2,3-dioloyloxy) propyl]-N,N,N-trimethylammonium methylsulfate (DT; DOTAP, Roche, Switzerland). PD is a newly developed Lp [23][24][25], whereas LF and DT are conventional ones used in previous studies [19,20]. As a DNA source, pGL3 control vector (Promega, USA), which was propagated and purified in 0.7-1.2 mg/mL plasmid, was used.…”
Section: Methodsmentioning
confidence: 99%
“…We have also shown that area-specific gene transfer is feasible with the improved system using the DNA-fibronectin-apatite composite layer (DF-Ap layer) [18]. More recently, Sun et al and Luong et al [19,20] have shown that conjugation of DNA with a lipid transfection reagent (Lp) is also effective in improving the gene transfer efficiency of the D-Ap layer. Although Lps employed in these studies are commercially available and have long been used worldwide because of their excellent efficiency for a non-viral system, they have the drawback of reduced efficiency in the presence of serum.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the gene transfer efficiency of the calcium phosphate system is relatively low. It was improved by developing a non-particulate and surface-mediated gene transfer system using a DNA-apatite composite layer (D-Ap layer), in which DNA molecules are immobilized within a matrix of apatite nanocrystals [13,14]. Recently, we have further improved the efficiency of gene transfer by co-immobilizing a cell adhesion protein, in this case either laminin [15,16] or fibronectin [17,18], within the D-Ap layer.…”
Section: Introductionmentioning
confidence: 99%